2015
DOI: 10.1161/hypertensionaha.114.04538
|View full text |Cite
|
Sign up to set email alerts
|

Impaired Neuronal Nitric Oxide Synthase–Mediated Vasodilator Responses to Mental Stress in Essential Hypertension

Abstract: Abstract-Neuronal NO synthase (nNOS) regulates blood flow in resistance vasculature at rest and during mental stress.To investigate whether nNOS signaling is dysfunctional in essential hypertension, forearm blood flow responses to mental stress were examined in 88 subjects: 48 with essential hypertension (42±14 years; blood pressure, 141±17/85±15 mm Hg; mean±SD) and 40 normotensive controls (38±14 years; 117±13/74±9 mm Hg). A subsample of 34 subjects (17 hypertensive) participated in a single blind 2-phase cro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 36 publications
1
9
0
Order By: Relevance
“…In the present study, SMTC reduced basal coronary flow, as previously documented ( 32 , 33 ), and substantially attenuated the mental stress-induced increase in blood flow. The degree of attenuation in stress-induced vasodilation is similar to that previously observed in the forearm ( 20 ), although it should be noted that subject characteristics were significantly different between these studies. The present study by necessity was undertaken in patients undergoing diagnostic coronary angiography and, therefore, included older patients with multiple risk factors for coronary disease and on oral medications.…”
Section: Discussionsupporting
confidence: 85%
“…In the present study, SMTC reduced basal coronary flow, as previously documented ( 32 , 33 ), and substantially attenuated the mental stress-induced increase in blood flow. The degree of attenuation in stress-induced vasodilation is similar to that previously observed in the forearm ( 20 ), although it should be noted that subject characteristics were significantly different between these studies. The present study by necessity was undertaken in patients undergoing diagnostic coronary angiography and, therefore, included older patients with multiple risk factors for coronary disease and on oral medications.…”
Section: Discussionsupporting
confidence: 85%
“…Similarly, Zanzinger et al (1997) also reported that inhibition of nNOS in the paraventricular nucleus could drive central sympathetic outflow, suggesting an important role of NO in the cardiac sympathetic neural axis (reviewed by Paton et al 2002;Danson et al 2009). Since then, it has gradually been recognized that NO dysregulation may play a major role in the aetiology of sympathetic hyperactivity in hypertension and other cardiovascular pathologies (Hamilton Gamboa et al 2012;Zhang et al 2014;Khan et al 2015). However, a detailed understanding of the cellular pathways underpinning the action of cyclic nucleotides and protein kinase regulation on cardiac neurotransmission in disease is still relatively poorly understood.…”
Section: Nitric Oxide-soluble Guanylate Cyclase-cgmp Signalling In Camentioning
confidence: 98%
“…; Khan et al . ). However, a detailed understanding of the cellular pathways underpinning the action of cyclic nucleotides and protein kinase regulation on cardiac neurotransmission in disease is still relatively poorly understood.…”
Section: Introductionmentioning
confidence: 97%
“…The forearm vasodilatation of mental stress is highly dependent on shear stress-induced release of NO and the β 2 -adrenoceptor effect of adrenaline, which is NO-dependent (Dietz et al 1994 ; Halliwill et al 1997 ; Seddon et al 2008 ). The NO-dependent component of stress-induced forearm vasodilatation was impaired in those with hypertensive parents, in hypertensives and in black African Americans (Cardillo et al 1998a , b ; Schlach et al 2002 ; Khan et al 2015 ). Thus, it is reasonable to propose that the majority of young SA men showed forearm vasoconstriction because their NO-dependent, and β 2 -adrenoceptor mediated dilatation was blunted.…”
Section: Discussionmentioning
confidence: 99%